Pengaruh Latihan Imagery dan Konsentrasi Terhadap Ketepatan Forehand Service Pada Pembinaan Prestasi Tenis Meja Universitas Tunas Pembangunan - Sunjoyo Sunjoyo; Satrio Sakti Rumpoko; Bagus Kuncoro; Erik Teguh Prakoso (Journal on Education, 2023)
This study aims to determine (1) The difference in the effect between internal imagery training method and external imagery training method on forehand service accuracy in Sukoharjo table tennis athletes. (2). The difference in the effect of high concentration and low concentration on the accuracy of forehand service in Sukoharjo table tennis athletes. (3). The interaction between the two imagery training methods and the concentration on the accuracy of forehand service in coaching table tennis achievements at Universitas Tunas TPembangunan University.The population in this study is all table tennis achievement coaching students of Universitas Tunas Pembangunan Surakarta. The sample used uses Total Sampling technique with the number of ... 24... student. This research is an experimental method using a 2x2 factorial design design, therefore this method is validation, which is testing the influence of one or more variables on other variables. . Data collection is carried out by test and measurement techniques, namely forehand service accuracy tests. Data analysis was carried out with a double comparison technique with a signification level of 0.05.The results of this study are (1) There is no significant difference in influence based on the results of the analysis, significant value p 0.049 (rounded significance value 0.05). Since the significance value of p is0.05 < 0.05, Ho is accepted. Thus, there was no significant difference in influence between the higher internal imagery training method (good) with a posttest average value of 23,583 compared to the external imagery training method with a posttest average value of 22,417. Thus, it was concluded that the hypothesis was rejected. (2) There is a significant difference in influence based on the results of the analysis, the significance value of p is 0.000. Since the significance value of p is 0.000< 0.05, Ho is rejected. Thus there is a significant difference in influence between athletes who have high concentration and low concentration. Based on the results of the analysis, there were students who had a higher high concentration (good) with a posttest average score of 24,917 compared to athletes who had low concentration with a posttest average score of 21,083. Thus, it was concluded that the hypothesis was accepted. (3) There is a significant interaction of both imagery training methods (internal imagery and external imagery) and concentration (high and low) on the accuracy of forehand service in Sukoharjo table tennis athletes. This can be seen from the significance value of p of 0.026. Therefore the significance value of p is 0.026 < 0.05, meaning Ho is rejected.